1975
DOI: 10.1111/j.1365-2389.1975.tb01938.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Relationship Between the Surface Properties of Chalk Soils and Slope Form Using Principal Components Analysis

Abstract: Five line transects were sited over grass-covered, convex-concave slopes in the Berkshire and Wiltshire chalk downs, with the object of describing and interpreting the variation in selected surface soil properties. Previous work had concentrated upon the correlation between single variables and slope gradient and slope length, whereas the emphasis of the present paper lies in examining the interrelationships amongst the variables through the use of principal components analysis.A consistent pattern of variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…A few significant PCs for explaining maximum variability in the data could often be better interpretable than the original data of many variables (Norris 1972). Such a dimensionality reduction would be an important economic consideration, especially if potential information recoverable from the transformed data is just as good as original data (Anderson and Furley 1975). The long-term sustainability of treatments could be assessed based on the procedure described by Maruthi Sankar et al (2011, 2012a, 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…A few significant PCs for explaining maximum variability in the data could often be better interpretable than the original data of many variables (Norris 1972). Such a dimensionality reduction would be an important economic consideration, especially if potential information recoverable from the transformed data is just as good as original data (Anderson and Furley 1975). The long-term sustainability of treatments could be assessed based on the procedure described by Maruthi Sankar et al (2011, 2012a, 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of soil acidity over the slope, with an acid/alkaline boundary (Figure 4), results from two different soil types and not a gradual upslope change. This illustrates the 'junction effect' described by Anderson and Furley (1975).…”
Section: Discussionmentioning
confidence: 89%
“…The Eigen values and variance (%) explained by PCs in model (2) Anderson and Furley (1975), the authors observed that capturing variability through a few significant PCs would be useful compared to a prediction model with many non-significant variables.…”
Section: Principal Component Modelmentioning
confidence: 96%
“…A few significant PCs for explaining maximum variability in the data could often be better interpretable than the original data of many variables (Norris, 1972). Such a reduction in the dimensionality would be an important economic consideration, especially if potential information recoverable from the transformed data is just as good as original data (Anderson and Furley, 1975). The long-term sustainability of treatments could be assessed based on the procedure described by Maruthi Sankar et al (2006Sankar et al ( , 2011Sankar et al ( , 2012a).…”
Section: Introductionmentioning
confidence: 99%